Omah Alas as an Adaptive Dwelling in Karst Area: Spatial Characteristics - Shabrina Tamimi; Dwita Hadi Rahmi (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2020)
The environmental condition of particular landscape contributes to the way of life of people living inside it. The characteristic of Gunung Sewu karst landscape in the south of Gunungkidul Regency causes the regular drought every year. The communities who live in the area, in which the majority of them work as traditional farmers, deal with such situations and gradually adapt to harmonize their lives with those conditions. In order to cultivate their land more intensively under the pressure of environmental conditions, the farmers build omah alas, a simple house to live around their field. Omah alas has characteristics as result of the relationship between people and landscape. This paper aims to identify the characteristics of omah alas as living space for traditional farmers in karst area, specifically in Kemadang Village, and the influencing factors. This research used qualitative approach and the data were collected by field observations and informant interviews. The results showed that there are three types of space layout that are caused by site conditions. The influence of spatial character is reinforced by economic motives.